Inuit knowledge of mammal distribution in Nunavut: Applications in wildlife management and risk assessment - Kowalchuk, Karen (University of Guelph, 2010)
Recovery strategies for species at risk can change harvesting quotas, directly affecting Inuit families and communities in Nunavut. Inuit knowledge (IK) of the environment is rich and complex, and integration of IK into wildlife management is mandated in Nunavut, but implementation has been challenging. Two spatial databases containing Nunavut Inuit harvest information were used to explore IK of mammals. IK distribution maps and quantitative range values of extent of occurrence (EO) and area of occupancy (AO) were derived. Range values were applied using the Canadian species at risk assessment process. Outputs were compared to information from western science (WSK) and existing species designations. IK derived distribution patterns were remarkably similar to WSK patterns; range values and status designations were not. It was concluded that there are major challenges within current risk assessment processes. IK data can contribute substantially to there and other wildlife management programs, leading to better decision making.